Assessment of 2013 AHA/ACC ASCVD risk scores with behavioral characteristics of an urban cohort in India: Preliminary analysis of Noncommunicable disease Initiatives and Research at AMrita (NIRAM) study. Issue 49 (December 2016) - Menon, Vidya P.; Edathadathil, Fabia; Sathyapalan, Dipu; Moni, Merlin; Don, Ann; Balachandran, Sabarish; Pushpa, Binny; Prasanna, Preetha; Sivaram, Nithu; Nair, Anupama; Vinod, Nithu; Jayaprasad, Rekha; et al.
Abstract : Abstract: Cardiovascular diseases (CVDs) are the leading cause of death and disability in India. Early and sustained exposure to behavioral risk factors leads to development of CVDs. The aim of this study was to determine the baseline risk of a "hard CVD event" in subjects attending comprehensive health clinic and assess behavioral characteristics in "at risk" population. Using WHO STEPwise approach to Surveillance modified questionnaire, prevalence of noncommunicable diseases (NCDs) and risk factors was estimated in this cross-sectional study of 4507 subjects. Baseline cardiovascular risk was determined using Framingham risk score (FRS) and American College of Cardiology (ACC)/American Heart Association (AHA) atherosclerotic cardiovascular disease (ASCVD) algorithms. Modifiable behavior associated with high CVD risk was assessed. Among 40 to 59-year olds, ASCVD risk tool derived both a 10-year and lifetime risk score, which were used to stratify the cohort into 3 risk groups, namely, a high 10-year and high lifetime, a low 10-year and high lifetime, and a low 10-year and low lifetime risks. Dyslipidemia (30.6%), hypertension (25.5%), diabetes mellitus (20%), and obstructive airway disorders (17.6%) were most prevalent NCDs in our cohort. The ASCVD score stratified 26.1% subjects into high 10-yr and 59.5% into high lifetime risk while FRS classified 17.2% into high 10-year risk. Compared with FRS, the ASCVD risk estimator identified a larger proportion of subjects "at risk" of developing CVD. A high prevalence of alcohol use (38.4%), decreased intake of fruits and vegetables (96.2%) and low physical activity (58%) were observed in "at risk" population. Logistic regression analysis showed that in 40 to 59-year group, regular and occasional drinkers were 8.5- and 3.1-fold more likely to be in high 10-year and high lifetime ASCVD risk category than in low 10-year and low lifetime risk group. Similarly, regular drinkers and occasional drinkers were 2.1 and 1.3 times more likely to be in low 10-year and high lifetime risk than in low 10-year and low lifetime risk category. Subjects with inadequate intake of fruits and vegetables were 1.59 times more likely to be in low 10-year and high lifetime risk than the lower 10-year and lifetime risk group. Obese participants were 2.3-fold more likely to be in low 10-year and high lifetime risk. Identification of "at risk" subjects from seemingly healthy population will allow sustainable primary prevention strategies to reduce CVD. Abstract : Supplemental Digital Content is available in the text